(untitled) (BISTUA Revista de la Facultad de Ciencias Básicas, 2025)
Microscopic life in the oceans—including bacteria, archaea, viruses, fungi, protozoa, and microalgae—is essential for the health of marine ecosystems. These microorganisms form the microbiome, a community that establishes symbiotic relationships with organisms such as corals, sea anemones, and jellyfish of the phylum Cnidaria. In these cases, the host–microbiome complex is known as a holobiont, where microbes provide defense against pathogens, produce antimicrobial compounds, and supply nutrients that optimize host metabolism and physiology. This review explores the ecological role of the microbiome in cnidarians and its response to environmental stress. A key example is the symbiosis with microalgae of the family Symbiodiniaceae, which provide photosynthetic products that support the host’s energy needs. However, climate change and pollution disrupt this relationship, leading to bleaching, symbiont loss, and microbiome destabilization. These changes favor the proliferation of pathogenic bacteria and can ultimately result in cnidarian death. The use of anemones, corals, and jellyfish as model systems is highlighted to study these processes, including the decline of beneficial bacteria such as Endozoicomonas and the increase of opportunistic pathogens like Vibrio. The presence of key bacteria such as Ruegeria, even under stressful conditions, is also emphasized. Overall, the microbiome emerges as a sentinel of marine health, reflecting environmental shifts before visible damage occurs and offering tools for conservation in the face of global warming.